COMPrehensive geriatric AsseSSment and multidisciplinary team intervention for hospitalised older adults (COMPASS): a protocol of pragmatic trials within a cohort. Issue 8 (1st August 2022) - Choi, Jung-Yeon; Lee, Ji Yeon; Shin, Jaeyong; Kim, Chang Oh; Kim, Kwang Joon; Hwang, In Gyu; Lee, Yun-Gyoo; Koh, Su-Jin; Hong, Soojung; Yoon, Sol-Ji; Kang, Min-gu; Kim, Jin Won; et al.
Abstract : Introduction: There is an increased demand for services for hospitalised older patients with acute medical conditions due to rapidly ageing population. The COMPrehensive geriatric AsseSSment and multidisciplinary team intervention for hospitalised older adults (COMPASS) study will test the effectiveness of comprehensive geriatric assessment (CGA) and multidisciplinary intervention by comparing it with conventional care among acute hospitalised older adults in Korea. Methods and analysis: A multicentre trial within a cohort comprising three substudies (randomised controlled trials) will be conducted. The intervention includes CGA and CGA-based multidisciplinary interventions by physicians (geriatricians, oncologists), nurses, nutritionists and pharmacists. The multidisciplinary intervention includes nutritional support, medication review and adjustment, rehabilitation, early discharge planning and prevention of geriatric syndromes (falls, delirium, pressure sore and urinary retention). The analysis will be based on an intention-to-treat principle. The primary outcome is living at home 3 months after discharge. In addition to assessing the economic effects of the intervention, a cost-utility analysis will be conducted. Ethics and dissemination: The study protocol was reviewed and approved by the ethics committees of Seoul National University Bundang Hospital and each study site. The study findings will be published in peer-reviewed journals. Subgroup and further in-depth analyses will subsequently be published. Trial registration number: KCT0006270.